Method for inhibiting the formation of diclofenac indolinone bodies

JP7640513B2Active Publication Date: 2025-03-05HISAMITSU PHARM CO INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022189155
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-11-28
Publication Date
2025-03-05
Estimated Expiration
2042-11-28

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、貼付剤において、ジクロフェナクインドリノン体の生成(特に保管時におけるジクロフェナクインドリノン体の生成)を抑制することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640513000001
    Figure 0007640513000001
  • Figure 0007640513000002
    Figure 0007640513000002
  • Figure 0007640513000003
    Figure 0007640513000003
Patent Text Reader

Abstract

To provide a method for inhibiting production of diclofenacindolinone derivatives in patches.SOLUTION: The present invention provides a method for inhibiting production of diclofenacindolinone derivatives in an adhesive layer within a patch, which consists of a support layer and the adhesive layer laminated on the support layer. This method includes the steps of: mixing diclofenac free acid, an adhesive base and oleic acid to obtain an adhesive composition; and forming the adhesive composition to obtain the patch. In the adhesive layer, a mass ratio between diclofenac free acid and oleic acid is 1:0.7-1:5.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for inhibiting the production of diclofenac indolinone derivatives. [Background technology]

[0002] Patches containing diclofenac, a type of nonsteroidal anti-inflammatory analgesic, are known to have analgesic and anti-inflammatory effects for diseases and symptoms such as lower back pain, shoulder periarthritis, cervicobrachial syndrome, tendonitis, peritendinitis, humeral epicondylitis (tennis elbow, etc.), muscle pain (myofascial lower back pain, etc.), and swelling and pain after trauma, as well as for analgesic and anti-inflammatory effects for various cancers, and have been extensively studied. For example, Patent Document 1 describes a patch that contains diclofenac or a pharma- ceutically acceptable salt thereof, citric acid, and dimethyl sulfoxide, and in which the mass ratio of diclofenac or a pharma-ceutically acceptable salt thereof to citric acid and the mass ratio of diclofenac or a pharma-ceutically acceptable salt thereof to dimethyl sulfoxide are within a specified range. Patent Document 2 describes an active substance-containing adhesive patch comprising an impermeable auxiliary membrane, diclofenac or a pharma- ceutically acceptable salt thereof, a matrix-forming polymer selected from styrene-isoprene-styrene block copolymers and ethylene-vinyl acetate copolymers, a tackifier consisting of an aliphatic hydrocarbon resin and a thermoplastic terpene resin, and one or more solvents selected from the group consisting of oleic acid and its derivatives, fatty acid alkyl esters, and N-alkyl-pyrrolidones, and a peelable protective membrane. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2013 / 191128 [Patent Document 2] Special Publication No. 2004-508397 Summary of the Invention [Problem to be solved by the invention]

[0004] Many of the diclofenac-containing patches that have been studied so far are patches containing a pharma- ceutically acceptable salt of diclofenac (specifically, diclofenac sodium). It is known that diclofenac indolinone, a type of decomposition product of diclofenac, is generated in patches containing a pharma-ceutically acceptable salt of diclofenac. In order to provide a highly stable patch, it is important to inhibit the generation of diclofenac indolinone. Therefore, the object of the present invention is to provide a method for inhibiting the generation of diclofenac indolinone in a patch. [Means for solving the problem]

[0005] The inventors have studied patches containing diclofenac free acid and found that a patch containing diclofenac free acid and oleic acid in a specified mass ratio is more capable of suppressing the production of diclofenac indolinone than a patch containing diclofenac sodium, thereby completing the present invention.

[0006] That is, the present invention provides a method for suppressing production of diclofenac indolinone in a patch comprising a support layer and an adhesive layer laminated on the support layer, the method comprising the steps of mixing diclofenac free acid, an adhesive base and oleic acid to obtain an adhesive composition, and forming the adhesive composition to obtain the patch, wherein the mass ratio of diclofenac free acid to oleic acid in the adhesive layer is 1:0.7 to 1:5. Effect of the Invention

[0007] According to the present invention, the production of diclofenac indolinone derivatives (particularly the production of diclofenac indolinone derivatives during storage) in a patch can be inhibited. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present invention will be described in detail below by showing embodiments of the present invention.

[0009] A method according to one embodiment of the present invention is a method for suppressing the production of diclofenac indolinone in a patch comprising a support layer and an adhesive layer laminated on the support layer, the method comprising the steps of mixing diclofenac free acid, an adhesive base and oleic acid to obtain an adhesive composition, and forming the adhesive composition to obtain the patch, wherein the mass ratio of diclofenac free acid to oleic acid in the adhesive layer is 1:0.7 to 1:5, thereby suppressing the production of diclofenac indolinone in the adhesive layer.

[0010] The support layer holds the adhesive layer. The support layer is preferably a monolayer or laminate of fibers in the form of cloth (woven, nonwoven, or knitted fabric) or a nonporous or porous film (sheet). The material of the support layer is preferably one or more materials selected from polyester (polyethylene terephthalate, polyethylene isophthalate, polypropylene terephthalate, polypropylene isophthalate, polybutylene terephthalate, polyethylene naphthalate, etc.), polyolefin (polymer or copolymer of vinyl monomers such as ethylene, propylene, vinyl acetate, or acrylonitrile), polyamide (nylon, silk, etc.), polyurethane, or cellulose (cotton, hemp, etc.). The cloth (woven, nonwoven, or knitted fabric) may be coated with a rubber composition. The rubber composition contains a rubber-based adhesive base. The rubber adhesive base is, for example, polyisoprene, polyisobutylene, polybutadiene, styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, styrene-butadiene rubber, styrene-isoprene rubber, or a combination thereof. The rubber composition may contain a tackifier resin. The tackifier resin is, for example, an alicyclic saturated hydrocarbon resin, a hydrogenated rosin glycerin ester, a terpene resin, or a combination thereof. The rubber composition may further contain additives such as a plasticizer and a filler. The thickness of the support layer is, for example, 0.1 mm to 2 mm. The basis weight of the support layer is, for example, 30 g / m 2 ~200g / m 2In this specification, the thickness and basis weight of the support layer are measured in accordance with the standard JIS L 1906:2000.

[0011] The moisture permeability of the support layer is 400g / m 2 - 24 hours or more is preferable, 1000g / m 2 More preferably, 24 hours or more, 4000g / m 2 It is even more preferable that the moisture permeability is 24 hours or more. When a support layer with such high moisture permeability is used, dimethyl sulfoxide gradually evaporates from the patch applied to the skin, improving the adhesiveness of the patch and making it less likely to peel off even when applied for a long period of time. The upper limit of moisture permeability is 20,000 g / m 2 24 hours. When the moisture permeability of the backing layer is in this range, dimethyl sulfoxide is more likely to volatilize from the adhesive layer, which is more effective in improving the adhesiveness of the patch. The moisture permeability of the backing layer means the moisture permeability at 40°C as defined in the JIS Z0208:1976 standard (Test method for moisture permeability of moisture-proof packaging material (cup method)).

[0012] When the backing layer is cloth-like, the 50% modulus (JIS L 1018:1999) in both the longitudinal direction (material flow direction) and lateral direction (material width direction) of the backing layer is preferably 1 N / 50 mm to 12 N / 50 mm. When the 50% modulus is 12 N / 50 mm or less, the stress that the patch receives due to the expansion and contraction of the skin is smaller, resulting in good adhesion to the skin.

[0013] When the support layer is a film, the material is preferably one having high moisture permeability (high dimethyl sulfoxide permeability) such as polyurethane. A film made of polyurethane is preferred from the viewpoint of enhancing the adhesion of the patch to the skin and the ability to follow the expansion and contraction of the patch, since it has excellent elasticity.

[0014] The support layer is preferably, for example, a nonwoven fabric or film made of polyurethane, a knitted fabric, nonwoven fabric or film made of polyethylene terephthalate, a polyester cloth coated with a rubber composition, or a combination thereof. More specifically, the support layer is more preferably a laminate of a film made of polyurethane and a nonwoven fabric made of polyurethane, a knitted fabric or nonwoven fabric made of polyethylene terephthalate, or a polyester cloth coated with a rubber composition.

[0015] The adhesive layer is formed from an adhesive composition obtained by mixing diclofenac free acid, an adhesive base, oleic acid, and optional ingredients described below. The total paste mass of the adhesive layer is 10 g / m2 or less in order to allow the patch to adhere appropriately to the skin. 2 ~1000g / m 2 is preferred, and 30 g / m 2 ~300g / m 2 More preferably, 100 g / m 2 ~250g / m 2 is more preferred.

[0016] Diclofenac free acid is a compound also known as 2-[(2,6-dichlorophenyl)amino]phenylacetic acid. The content of diclofenac free acid is 0.5% by mass to 8% by mass, and may be 1% by mass to 7% by mass, 1% by mass to 5% by mass, or 1% by mass to 4.65% by mass, based on the total mass of the adhesive layer.

[0017] The adhesive base is for imparting adhesiveness to the adhesive layer, and examples thereof include rubber-based adhesive bases, acrylic-based adhesive bases, and silicone-based adhesive bases. The adhesive base is preferably at least one selected from the group consisting of rubber-based adhesive bases, acrylic-based adhesive bases, and silicone-based adhesive bases. The adhesive base is preferably free of water (non-aqueous adhesive base). The adhesive base may be any one of rubber-based adhesive bases, acrylic-based adhesive bases, and silicone-based adhesive bases, or a combination thereof. The total content of the adhesive base may be 10% by mass to 90% by mass, or may be 20% by mass to 90% by mass, based on the total mass of the adhesive layer.

[0018] Examples of the rubber-based adhesive base include natural rubber, polyisobutylene, alkyl vinyl ether (co)polymer, polyisoprene, polybutadiene, styrene-butadiene copolymer, styrene-isoprene copolymer, styrene-isoprene-styrene block copolymer, styrene-butadiene-styrene block copolymer, etc. The rubber-based adhesive base may be used alone or in combination of two or more of these. Among them, the rubber-based adhesive base according to the present embodiment is preferably at least one selected from the group consisting of styrene-isoprene-styrene block copolymer and polyisobutylene, and more preferably styrene-isoprene-styrene block copolymer, or styrene-isoprene-styrene block copolymer and polyisobutylene, from the viewpoint that the adhesive layer tends to exhibit more sufficient adhesive strength.

[0019] Specific examples of styrene-isoprene-styrene block copolymers include Quintac (registered trademark) 3570C (trade name, manufactured by Zeon Corporation), SIS5002, SIS5229, SIS5505, SIS5505P (trade names, manufactured by JSR Corporation), and SIBSTAR (registered trademark) T102 (trade name, manufactured by Kaneka Corporation). Polyisobutylene also includes so-called butyl rubber (isobutylene-isoprene rubber), and a specific example thereof is Oppanol (registered trademark). ) N50, N80, N100, N150, B11, B12, B50, B80, B100, B120, B150, B220 (trade names, manufactured by BASF), JSR (registered trademark) Butyl 065, 268, 365 (trade names, manufactured by JSR Corporation), X_Butyl (registered trademark) RB100, 101-3, 301, 402 (trade names, manufactured by ARLANXEO), Exxon (registered trademark) Butyl 065, 065S, 068, 068S, 268, 268S, 365, 365S (trade names, manufactured by Exxon Mobile), Butyl 065, 268, 365 (trade names, manufactured by Japan Butyl Co., Ltd.), and the like.

[0020] The content of the rubber-based adhesive base can be 10% by mass to 90% by mass, or may be 15% by mass to 60% by mass, 15% by mass to 40% by mass, or 15% by mass to 30% by mass, based on the total mass of the adhesive layer. When a mixture of a styrene-isoprene-styrene block copolymer and polyisobutylene is used as the rubber-based adhesive base, the mass ratio of the two is preferably 4:1 to 1:4, 3:1 to 1:1, or 3:1 to 2:1.

[0021] The acrylic adhesive base is a component that imparts adhesiveness to the adhesive layer, and is, for example, a (co)polymer of one or more (meth)acrylic acid alkyl esters. Examples of (meth)acrylic acid alkyl esters include butyl (meth)acrylate, isobutyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and decyl (meth)acrylate. In this specification, the term "(meth)acrylic acid" means either one or both of acrylic acid and methacrylic acid, and similar expressions are defined in the same manner.

[0022] The acrylic adhesive base may be a copolymer formed from an alkyl (meth)acrylate ester (main monomer) and a comonomer. Examples of the main monomer include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. One of these may be used alone, or two or more may be used in combination. The comonomer may be any component that can be copolymerized with an alkyl (meth)acrylate ester. Examples of the comonomer include hydroxyalkyl (meth)acrylate ester, ethylene, propylene, styrene, vinyl acetate, N-vinylpyrrolidone, (meth)acrylic acid, and (meth)acrylic acid amide. The comonomer may be one type alone, or two or more may be used in combination.

[0023] Specific examples of acrylic adhesive bases include acrylic acid / octyl acrylate copolymer, 2-ethylhexyl acrylate / vinylpyrrolidone copolymer solution, acrylic ester / vinyl acetate copolymer, 2-ethylhexyl acrylate / 2-ethylhexyl methacrylate / dodecyl methacrylate copolymer, methyl acrylate / 2-ethylhexyl acrylate copolymer resin emulsion, and acrylic polymers contained in acrylic resin alkanolamine solution. Specific examples of such acrylic adhesive bases include the DURO-TAK series (manufactured by Henkel) such as DURO-TAK (registered trademark) 387-2510, DURO-TAK (registered trademark) 87-2510, DURO-TAK (registered trademark) 387-2287, DURO-TAK (registered trademark) 87-2287, DURO-TAK (registered trademark) 87-4287, DURO-TAK (registered trademark) 387-2516, DURO-TAK (registered trademark) 87-2516, DURO-TAK (registered trademark) 87-2074, DURO-TAK (registered trademark) 87-900A, DURO-TAK (registered trademark) 87-901A, DURO-TAK (registered trademark) 87-9301, and DURO-TAK (registered trademark) 87-4098; GELVA (registered trademark) GMS 788, GELVA (registered trademark) GMS Examples of such series include the GELVA series (manufactured by Henkel), such as GELVA 3083 and GELVA (registered trademark) GMS 3253; the MAS series (manufactured by Cosmedi Pharmaceutical Co., Ltd.), such as MAS811 (product name) and MAS683 (product name); the Eudragit (registered trademark) series (manufactured by Evonik), the Nikasol (registered trademark) series (manufactured by Nippon Carbide Industries Co., Ltd.), and the Ultrasol (registered trademark) series (manufactured by Aica Kogyo Co., Ltd.).

[0024] The content of the acrylic adhesive base can be 10% by mass to 90% by mass, and may be 20% by mass to 90% by mass, based on the total mass of the adhesive layer.

[0025] The silicone adhesive base is a compound having an organopolysiloxane skeleton, and examples of the silicone adhesive base include dimethylpolysiloxane, polymethylvinylsiloxane, and polymethylphenylsiloxane. Specific examples of silicone adhesive bases include MD series such as MD7-4502 Silicone Adhesive and MD7-4602 Silicone Adhesive (manufactured by DuPont Toray Specialty Materials Co., Ltd.); BIO-PSA (registered trademark) 7-4301 Silicone Adhesive, BIO-PSA (registered trademark) 7-4302 Silicone Adhesive, BIO-PSA (registered trademark) 7-4201 Silicone Adhesive, BIO-PSA (registered trademark) 7-4202 Silicone Adhesive, BIO-PSA (registered trademark) 7-4101 Silicone Adhesive, BIO-PSA (registered trademark) 7-4102 Silicone Adhesive, BIO-PSA (registered trademark) 7-4601 Silicone Adhesive, BIO-PSA (registered trademark) 7-4602 Silicone Adhesive, and BIO-PSA (registered trademark) 7-4501 Silicone Examples of such adhesives include the BIO-PSA series (manufactured by DuPont-Toray Specialty Materials Co., Ltd.), such as BIO-PSA (registered trademark) 7-4502 Silicone Adhesive, BIO-PSA (registered trademark) 7-4401 Silicone Adhesive, and BIO-PSA (registered trademark) 7-4402 Silicone Adhesive; Dow Corning (registered trademark) 7-9800A, Dow Corning (registered trademark) 7-9800B, Dow Corning (registered trademark) 7-9700A, and Dow Corning (registered trademark) 7-9700B.

[0026] The content of the silicone-based adhesive base can be 10% by mass to 90% by mass, and may be 20% by mass to 90% by mass, based on the total mass of the adhesive layer.

[0027] The adhesive layer may further contain dimethyl sulfoxide for the purpose of dissolving diclofenac free acid and improving its skin permeability, etc. The content of dimethyl sulfoxide is preferably 1% by mass to 20% by mass, 1% by mass to 7% by mass, 2% by mass to 10% by mass, 3% by mass to 10% by mass, or 4% by mass to 8% by mass based on the total mass of the adhesive layer.

[0028] The ratio of diclofenac free acid to dimethyl sulfoxide is preferably 1:0.3 to 1:14, 1:0.4 to 1:7, 1:0.6 to 1:3, or 1:0.7 to 1:3 from the viewpoint of improving the skin permeability of diclofenac free acid and preventing precipitation of diclofenac crystals.

[0029] The content of oleic acid is 0.35% by mass to 40% by mass, and may be 0.5% by mass to 20% by mass, 1% by mass to 10% by mass, 2% by mass to 8% by mass, 3% by mass to 7% by mass, or 4% by mass to 6% by mass, based on the total mass of the adhesive layer.

[0030] In order to suppress the production of diclofenac indolinone, the mass ratio of diclofenac free acid to oleic acid in the adhesive layer is 1:0.7 to 1:5, preferably 1:1 to 1:5, more preferably 1:1.5 to 1:5, and particularly preferably 1:3 to 1:5.

[0031] The adhesive layer may further contain other additives as desired, such as a tackifier resin, a plasticizer, an absorption promoter, a solubilizer, a stabilizer, a filler, and a fragrance.

[0032] The tackifier resin is a component that adjusts the adhesiveness of the adhesive layer. Examples of the tackifier resin include petroleum resins, terpene resins, rosin resins, phenolic resins, and xylene resins. Examples of the petroleum resin include alicyclic petroleum resins (alicyclic saturated hydrocarbon resins, etc.), aliphatic petroleum resins (aliphatic hydrocarbon resins, etc.), and aromatic petroleum resins. More specifically, Arcon P-70, Arcon P-85, Arcon P-90, Arcon P-100, Arcon P-115, Arcon P-125, Arcon M-70, Arcon M-85, Arcon M-90, Arcon M-100, Arcon M-115, and Arcon M-125 (all trade names, manufactured by Arakawa Chemical Industries Co., Ltd.), and Escoretz 8000 (trade name, manufactured by Esso Petrochemical Co., Ltd.). Examples of terpene resins include pinene polymers (α-pinene polymer, β-pinene polymer, etc.), terpene polymers, dipentene polymers, terpene-phenol polymers, aromatic modified terpene polymers, and pinene-phenol copolymers. More specific examples include YS Resin (YS Resin PXN (1150N, 300N), YS Resin PX1000, YS Resin TO125, YS Resin TO105, etc.), Clearon P105, Clearon M115, Clearon K100 (all trade names, manufactured by Yasuhara Chemical Co., Ltd.), and Tamanol 901 (trade name, manufactured by Arakawa Chemical Industries, Ltd.). Examples of rosin resins include hydrogenated rosin glycerin ester, very light-colored rosin, very light-colored rosin ester, and acid-modified very light-colored rosin. More specifically, Pine Crystal (KE-311, PE-590, KE-359, KE-100, etc.) (trade name, manufactured by Arakawa Chemical Industries, Ltd.) and the like can be mentioned. The tackifier resin may be one of these alone or two or more of them in combination. Among them, alicyclic saturated hydrocarbon resin, terpene resin, hydrogenated rosin glycerin ester, or a combination thereof is preferable, and alicyclic saturated hydrocarbon resin, hydrogenated rosin glycerin ester, or a combination thereof is more preferable. When the adhesive layer contains a tackifier resin, the content of the tackifier resin can be 15% by mass to 80% by mass, and may be 30% by mass to 65% by mass, based on the total mass of the adhesive layer.When an alicyclic saturated hydrocarbon resin and a hydrogenated rosin glycerin ester are used as the tackifier resin, the mass ratio of the two is preferably 4:1 to 1:4, 4:1 to 2:3, or 3:1 to 2:1.

[0033] Examples of the plasticizer include paraffin oil (liquid paraffin, etc.), squalane, squalene, vegetable oils (olive oil, camellia oil, castor oil, tall oil, peanut oil, spearmint oil, eucalyptus oil, jojoba oil, camphor white oil, sunflower oil, orange oil, etc.), fats and oils (dibutyl phthalate, dioctyl phthalate, etc.), and liquid rubber (liquid polybutene, liquid isoprene rubber, etc.). A preferred plasticizer is liquid paraffin. One type of plasticizer may be used alone, or two or more types may be used in combination. When the adhesive layer contains a plasticizer, the content of the plasticizer is, for example, 3% by mass to 50% by mass, 5% by mass to 30% by mass, or 7% by mass to 20% by mass based on the total mass of the adhesive layer.

[0034] The absorption enhancer may be any compound that has been known to have a transdermal absorption enhancing effect. Examples of the absorption enhancer include organic acids (excluding oleic acid) and their salts (e.g., aliphatic carboxylic acids having 6 to 20 carbon atoms (hereinafter also referred to as "fatty acids") and their salts, cinnamic acid and its salts), organic acid esters (e.g., fatty acid esters, cinnamic acid esters), organic acid amides (e.g., fatty acid amides), aliphatic alcohols, polyhydric alcohols, ethers (e.g., aliphatic ethers, polyoxyethylene alkyl ethers), and the like. These absorption enhancers may have unsaturated bonds and may have a cyclic, linear, or branched chemical structure. In addition, the absorption enhancer may be a monoterpene compound, a sesquiterpene compound, or a vegetable oil (e.g., olive oil). These absorption enhancers may be used alone or in combination of two or more.

[0035] Examples of such organic acids include aliphatic (mono, di or tri) carboxylic acids (e.g., acetic acid, propionic acid, isobutyric acid, caproic acid, caprylic acid, fatty acids, lactic acid, maleic acid, pyruvic acid, oxalic acid, succinic acid, tartaric acid, etc.), aromatic carboxylic acids (e.g., phthalic acid, salicylic acid, benzoic acid, acetylsalicylic acid, etc.), cinnamic acid, alkanesulfonic acids (e.g., methanesulfonic acid, ethanesulfonic acid, propanesulfonic acid, butanesulfonic acid), alkylsulfonic acid derivatives (e.g., polyoxyethylene alkyl ether sulfonic acid, N-2-hydroxyethylpiperazine-N'-2-ethanesulfonic acid), and cholic acid derivatives (e.g., dehydrocholic acid, etc.). These organic acids may be alkali metal salts such as sodium salts. Among them, aliphatic carboxylic acids, aromatic carboxylic acids or their salts are preferred, and acetic acid or sodium acetate is particularly preferred. Examples of fatty acids include lauric acid, myristic acid, palmitic acid, stearic acid, isostearic acid, linoleic acid, and linolenic acid.

[0036] In another embodiment, the adhesive layer does not contain citric acid (including anhydrous citric acid) and its salts. A patch having an adhesive layer that does not contain citric acid and its salts further suppresses the production of diclofenac indolinone.

[0037] Examples of organic acid esters include ethyl acetate, propyl acetate, cetyl lactate, lauryl lactate, methyl salicylate, ethylene glycol salicylate, methyl cinnamate, and fatty acid esters. Examples of fatty acid esters include methyl laurate, hexyl laurate, isopropyl myristate, myristyl myristate, octyldodecyl myristate, isopropyl palmitate, and cetyl palmitate. The fatty acid ester may be glycerin fatty acid ester, propylene glycol fatty acid ester, sorbitan fatty acid ester, polyethylene glycol sorbitan fatty acid ester, polyethylene glycol fatty acid ester, sucrose fatty acid ester, or polyoxyethylene hydrogenated castor oil. Specific examples of fatty acid esters include glycerin monocaprylate, glycerin monocaprate, glycerin monolaurate, glycerin monooleate, sorbitan monolaurate, sucrose monolaurate, polysorbate 20, propylene glycol monolaurate, polyethylene glycol monolaurate, polyethylene glycol monostearate, Span 40, Span 60, Span 80, Span 120 (product names, manufactured by Croda Japan Co., Ltd.), Tween (registered trademark) 20, Tween (registered trademark) 21, Tween (registered trademark) 40, Tween (registered trademark) 60, Tween (registered trademark) 80, and NIKKOL (registered trademark) HCO-60 (product name, manufactured by Nikko Chemicals Co., Ltd.).

[0038] Examples of organic acid amides include fatty acid amides (such as lauric acid diethanolamide), hexahydro-1-dodecyl-2H-azepin-2-one (also called Azone) and its derivatives, and pyrothiodecane.

[0039] The term "aliphatic alcohol" refers to an aliphatic alcohol having 6 to 20 carbon atoms. Examples of the aliphatic alcohol include lauryl alcohol, myristyl alcohol, oleyl alcohol, isostearyl alcohol, and cetyl alcohol. Examples of the polyhydric alcohol include propylene glycol.

[0040] The aliphatic ether means an ether having an aliphatic group (for example, an alkyl group, an alkenyl group) having 6 to 20 carbon atoms. An example of the polyoxyethylene alkyl ether is polyoxyethylene lauryl ether.

[0041] Examples of the monoterpene compounds include geraniol, thymol, terpineol, l-menthol, borneol, d-limonene, isoborneol, nerol, and dl-camphor. As the monoterpene compound, peppermint oil may be used.

[0042] When the pressure-sensitive adhesive layer contains an absorption enhancer, the content of the absorption enhancer can be 2% by mass to 40% by mass based on the total mass of the pressure-sensitive adhesive layer.

[0043] The dissolving agent is a component that makes it easy to dissolve diclofenac free acid in the adhesive composition. Examples of the dissolving agent include fatty acid alkyl esters (e.g., isopropyl myristate, isopropyl palmitate), fatty acid polyhydric alcohol esters (e.g., propylene glycol monolaurate, glycerin monolaurate, glycerin monooleate, sorbitan monolaurate), fatty acid amides (e.g., diethanolamide laurate), fatty alcohols (e.g., octyldodecanol, isostearyl alcohol, oleyl alcohol), polyhydric alcohols (e.g., propylene glycol, dipropylene glycol, polyethylene glycol), pyrrolidone derivatives (e.g., N-methyl-2-pyrrolidone), and amines (e.g., triethanolamine, diethanolamine, monoethanolamine, diisopropanolamine, trometamol, meglumine). The dissolving agent may be used alone or in combination of two or more. When the pressure-sensitive adhesive layer contains a solubilizing agent, the content of the solubilizing agent can be 2% by mass to 40% by mass based on the total mass of the pressure-sensitive adhesive layer.

[0044] The stabilizer may be any agent capable of suppressing the generation of free radicals generated by the action of light such as ultraviolet rays, heat, or active chemical species, and the progression of the chain reaction thereof. Examples of the stabilizer include tocopherol and its ester derivatives, ascorbic acid and its ester derivatives, 2,6-dibutylhydroxytoluene, butylhydroxyanisole, and 2-mercaptobenzimidazole. The stabilizer may be used alone or in combination of two or more. When the adhesive layer contains a stabilizer, the content of the stabilizer may be 0.05% by mass to 3% by mass, or may be 0.05% by mass to 1% by mass, 0.05% by mass to 0.25% by mass, or 0.1% by mass to 0.25% by mass, based on the total mass of the adhesive layer.

[0045] Examples of the filler include powders of metal compounds (aluminum oxide, aluminum hydroxide, zinc oxide, titanium oxide, calcium carbonate, etc.), ceramics (talc, clay, kaolin, silica, hydroxyapatite, synthetic aluminum silicate, magnesium aluminometasilicate, etc.), or organic compounds (cellulose powder, stearates, etc.), or short fibers of resins containing these. One type of filler may be used alone, or two or more types may be used in combination. When the pressure-sensitive adhesive layer contains a filler, the content of the filler can be 0.1% by mass to 20% by mass based on the total mass of the pressure-sensitive adhesive layer.

[0046] The patch may further comprise a release liner. The release liner is laminated on the surface of the adhesive layer opposite to the support. The release liner tends to reduce adhesion of dirt and the like to the adhesive layer during storage. The surface of the release liner that comes into contact with the adhesive layer is preferably release-treated with silicone, fluorinated polyolefin, or the like.

[0047] The material of the release liner is not particularly limited, and liners generally known to those skilled in the art can be used. Examples of the release liner include paper; polyesters such as polyethylene terephthalate and polyethylene naphthalate; polyolefins such as polyethylene and polypropylene; and films such as polyvinyl chloride, polyvinylidene chloride, nylon, and aluminum. The release liner may be a laminate film of high-quality paper and polyolefin. The material of the release liner is preferably a film made of polypropylene or polyethylene terephthalate.

[0048] The patch can be produced, for example, by the following method. First, the components constituting the adhesive layer are mixed in a predetermined ratio to obtain a uniform solution (adhesive composition). Next, the adhesive composition is spread on a peelable film (release liner) or support layer at a predetermined paste mass to form an adhesive layer. Next, the adhesive layer is pressed onto the support layer or peelable film so that the adhesive layer is sandwiched between the peelable film and the support layer. Finally, the patch can be obtained by cutting into a desired shape. In this case, the release liner is removed when the patch is applied.

[0049] The patch area is 5 to 200 cm 2 30 to 100 cm 2 The shape and dimensions of the patch may be, for example, a rectangle with a short side of 3 to 14 cm and a long side of 7 to 20 cm, or a circle with a diameter of 1 to 10 cm. EXAMPLES

[0050] Experiment 1: Evaluation of the formation rate of diclofenac indolinone bodies in patches using rubber-based adhesive bases 1. Preparation of Patches A pressure-sensitive adhesive composition was obtained by mixing the components according to the following Table 1. The pressure-sensitive adhesive composition thus obtained was applied onto a release liner (a polyethylene terephthalate film subjected to a release treatment) so that the paste mass per unit area was 214 g / m 2A support layer (knitted fabric made of polyethylene terephthalate) was laminated on the opposite surface of the obtained adhesive layer to obtain a patch laminated in the order of support layer / adhesive layer / release liner.

[0051] 2. Measurement of diclofenac indolinone content The content of diclofenac indolinone was measured according to the following procedure using the patch immediately after production and the patch that had been stored in an aluminum packaging bag at 60°C for one week after production. First, the adhesive layer of the patch was removed and immersed in 2 mL of acetone to extract organic matter. Next, 6 mL of a dilution solution (0.1% phosphoric acid aqueous solution / methanol = 60 / 40 (v / v)) was added to make the total volume 8 mL, and after filtering insoluble matters, a chromatogram in which the peaks of diclofenac free acid and diclofenac indolinone were separated was obtained by high performance liquid chromatography under the following analytical conditions. The content of diclofenac indolinone was calculated from the value of the area under the peak curve corresponding to diclofenac indolinone, assuming the theoretical amount of diclofenac free acid to be 100. <Analysis conditions> Column: YMC-PacK Pro C8 Mobile phase: 0.1% phosphoric acid aqueous solution / methanol = 60 / 40 (v / v) Measurement wavelength: 275nm Flow rate: 1mL / min Sample injection volume: 30 μL Column temperature: 40℃

[0052] [Table 1]

[0053] It was confirmed that the patches of Examples 1 to 4, which contain diclofenac free acid and oleic acid and have a mass ratio of diclofenac free acid to oleic acid of 1:0.71 to 1:5, are more capable of suppressing the production of diclofenac indolinone than the patch of Comparative Example 1, which contains diclofenac sodium. It was also confirmed that the patch of Comparative Example 2, which has a mass ratio of diclofenac free acid to oleic acid of 1:0.5, cannot suppress the production of diclofenac indolinone.

[0054] Experiment 2: Evaluation of the formation rate of diclofenac indolinone derivatives in patches using acrylic adhesive base 1. Preparation of Patches The components were mixed according to Table 2 below to obtain a pressure-sensitive adhesive composition. The obtained pressure-sensitive adhesive composition was applied onto a release liner (a polyethylene terephthalate film subjected to a release treatment) so that the paste mass per unit area was 120 g / m 2 The solvent was then dried and removed to form an adhesive layer. A support layer (a polyethylene terephthalate film) was laminated on the opposite surface of the obtained adhesive layer to obtain a patch laminated in the order of support layer / adhesive layer / release liner.

[0055] 2. Measurement of diclofenac indolinone content Measurements were performed in the same manner as in Experiment 1.

[0056] [Table 2]

[0057] Even when an acrylic adhesive base was used, it was confirmed that the patch of Example 5, which contains diclofenac free acid and oleic acid and has a mass ratio of diclofenac free acid to oleic acid of 1:1.08, was more capable of suppressing the production of diclofenac indolinone derivatives than the patch of Comparative Example 3, which contains diclofenac sodium.

[0058] Experiment 3: Evaluation of the formation rate of diclofenac indolinone bodies in patches using silicone adhesive bases 1. Preparation of Patches Similar to Experiment 2, patches were prepared according to the composition in Table 3 below. However, in this example, the mass of the paste per unit area was 160 g / m 2 It was expanded so that

[0059] 2. Measurement of diclofenac indolinone content Measurements were performed in the same manner as in Experiment 1.

[0060] [Table 3]

[0061] Even when a silicone-based adhesive base was used, it was confirmed that the patch of Example 6, which contains diclofenac free acid and oleic acid and has a mass ratio of diclofenac free acid to oleic acid of 1:1.08, was more capable of suppressing the production of diclofenac indolinone derivatives than the patch of Comparative Example 4, which contains diclofenac sodium.

[0062] Experiment 4: Evaluation of the formation rate of diclofenac indolinone bodies in patches not containing polyisobutylene 1. Preparation of Patches Similar to Experiment 1, patches were produced according to the composition in Table 4 below.

[0063] 2. Measurement of diclofenac indolinone content Measurements were performed in the same manner as in Experiment 1.

[0064] [Table 4]

[0065] Even when polyisobutylene was not contained, it was confirmed that the patch of Example 7, which contains both diclofenac free acid and oleic acid and has a mass ratio of diclofenac free acid to oleic acid of 1:1.08, was more capable of suppressing the production of diclofenac indolinone compounds than the patch of Comparative Example 1, which contains diclofenac sodium. It was also confirmed that the patch of Example 7 had the same production rate of diclofenac indolinone compounds as the patches of Examples 1 to 4.

[0066] Experiment 5: Evaluation of the formation rate of diclofenac indolinone bodies in patches using acrylic or silicone adhesive bases 1. Preparation of Patches

[0067] Similarly to Experiment 2, patches of Examples 8 and 9 were produced according to the compositions in Table 5 below. Similarly to Experiment 3, patches of Examples 10 and 11 were produced according to the compositions in Table 5 below. 2. Measurement of diclofenac indolinone content Measurements were performed in the same manner as in Experiment 1.

[0068] [Table 5]

[0069] Even when an acrylic adhesive base or a silicone adhesive was used, it was confirmed that the patches of Examples 8 to 10, in which the mass ratio of diclofenac free acid to oleic acid in the adhesive layer was changed within the range of 1:0.71 to 1:5, were able to suppress the production of diclofenac indolinone compounds, compared with the patches of Comparative Examples 3 and 4, which contained diclofenac sodium. It was also confirmed that the patch of Example 11, which used a silicone adhesive base different from that of Example 6, was able to suppress the production of diclofenac indolinone compounds more effectively than the patch of Comparative Example 4, which contained diclofenac sodium.

Claims

[Claim 1] A method for suppressing production of diclofenac indolinone in a patch comprising a support layer and an adhesive layer laminated on the support layer, comprising: The method includes the steps of: mixing diclofenac free acid, an adhesive base, and oleic acid to obtain an adhesive composition; and forming the adhesive composition to obtain the patch. The method, wherein the mass ratio of diclofenac free acid to oleic acid in the adhesive layer is 1:0.7 to 1:5.

Citation Information

Patent Citations

  • Method for making pressure-sensitive adhesive matrix patches containing hydrophilic salts of drugs

    JP2003520191A

  • Diclofenac-containing transdermal patch

    JP2004508397A

  • Cataplasm product

    JP2008061862A

  • External preparation for percutaneous administration containing nonsteroidal Anti-inflammatory analgesic

    JP2011121980A

  • Patch

    JP2019055928A